Analisis Program Membership dan Kualitas Pelayanan pada Apotek Jetak Farma - Marsono; Ayatin, Hidayati Mu’immah; Saputra, Nurdiansyah Rico; Rohmah , Sinta Nur; Muzaki , Nofi Afan (TEKNOBIS : Jurnal Teknologi, Bisnis dan Pendidikan, 2026)
This study was conducted to measure the effectiveness and quality of service and membership at Jetak Farma Pharmacy. This study aims to provide a case study that allows customers to further reference each service program available at a retail store, especially Jetak Farma Pharmacy. The Indonesian retail industry has shown positive growth, prompting retailers to compete to develop their businesses by innovating and adapting to digital technology. The research method used to gather relevant information was qualitative interviews. Our team and I conducted interviews with practitioners in the field to gather information related to service and membership. The results of our data collection demonstrate how service quality and customer engagement are vital to driving progress in the retail business.